2007
DOI: 10.1186/1471-2164-8-38
|View full text |Cite
|
Sign up to set email alerts
|

A distinct epigenetic signature at targets of a leukemia protein

Abstract: Background: Human myelogenous leukemia characterized by either the non random t(8; 21)(q22; q22) or t(16; 21)(q24; q22) chromosome translocations differ for both their biological and clinical features. Some of these features could be consequent to differential epigenetic transcriptional deregulation at AML1 targets imposed by AML1-MTG8 and AML1-MTG16, the fusion proteins deriving from the two translocations. Preliminary findings showing that these fusion proteins lead to transcriptional downregulation of AML1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…This seemingly controversial result might possibly be explained by a context dependent gene regulation, since Wotton et al used 3T3 murine fibroblast cells in their experiments. In line with our data, PTPRCAP transcription was found to be repressed by RUNX1-MTG8 and - MTG16 fusion genes, two RUNX1 fusions that are frequently found in acute myeloid leukemia [14]. Furthermore, the regulation of two other genes that are differentially expressed in E/R -positive ALL, also concords with our E/R KD results.…”
Section: Resultssupporting
confidence: 92%
“…This seemingly controversial result might possibly be explained by a context dependent gene regulation, since Wotton et al used 3T3 murine fibroblast cells in their experiments. In line with our data, PTPRCAP transcription was found to be repressed by RUNX1-MTG8 and - MTG16 fusion genes, two RUNX1 fusions that are frequently found in acute myeloid leukemia [14]. Furthermore, the regulation of two other genes that are differentially expressed in E/R -positive ALL, also concords with our E/R KD results.…”
Section: Resultssupporting
confidence: 92%
“…The aberrant AML1-MTG fusion proteins retain the ability of interplaying with both repressor proteins and/or histone modifying enzymes, and can induce an altered epigenetic status at the chromatin of both coding and non-coding AML1-target genes [ 26 , 27 , 45 ]. Apparently, the fusion of two MTGs, MTG8 and MTG16, to the RHD region of AML1 does not affect the in vitro RNA-binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…AE014133 ) (Ajdic et al, 2002 ) and identified an interesting phenomenon: the rnc gene is located on upstream of vicRKX tricistronic operon. It is suggested that genes located nearby are functionally related and make up a part of a metabolic pathway (Okuda et al, 2007 ). Thus, we hypothesize that rnc may be involved in the regulation of exopolysaccharide synthesis.…”
Section: Introductionmentioning
confidence: 99%